2009
DOI: 10.1073/pnas.0900358106
|View full text |Cite
|
Sign up to set email alerts
|

The organic cation transporter-3 is a pivotal modulator of neurodegeneration in the nigrostriatal dopaminergic pathway

Abstract: Toxic organic cations can damage nigrostriatal dopaminergic pathways as seen in most parkinsonian syndromes and in some cases of illicit drug exposure. Here, we show that the organic cation transporter 3 (Oct3) is expressed in nondopaminergic cells adjacent to both the soma and terminals of midbrain dopaminergic neurons. We hypothesized that Oct3 contributes to the dopaminergic damage by bidirectionally regulating the local bioavailability of toxic species. Consistent with this view, Oct3 deletion and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
173
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 39 publications
13
173
0
Order By: Relevance
“…We recently reported that Oct3 can modulate toxicity in the dopaminergic system through its bidirectional transport capability of various toxic cations (12). In the present study, we asked whether this mechanism was also relevant to PQ 2+ .…”
Section: Pq 2+ Induces Striatal Neurotoxicity and Da Overflow In Micementioning
confidence: 80%
See 3 more Smart Citations
“…We recently reported that Oct3 can modulate toxicity in the dopaminergic system through its bidirectional transport capability of various toxic cations (12). In the present study, we asked whether this mechanism was also relevant to PQ 2+ .…”
Section: Pq 2+ Induces Striatal Neurotoxicity and Da Overflow In Micementioning
confidence: 80%
“…This lack of DA reduction in wild-type mice despite a loss of DA neurons is proposed to be related to the compensatory up-regulation of TH activity in the striatum after PQ 2+ injection (9). On the basis of our previously proposed function of Oct3 in mediating the neurotoxicity of methamphetamine (12), it is possible that the striatal neurotoxicity observed in the Oct3 −/− mice was due to a reduced PQ buffering capacity in non-DA cells, and, hence, more PQ was available for DAT-mediated transport into DA terminals. To lend further support for this argument, we performed in vivo microdialysis to compare the functional effects of PQ 2+ treatment in freely moving Oct3 −/− and Oct3 +/+ mice.…”
Section: Pq 2+ Induces Striatal Neurotoxicity and Da Overflow In Micementioning
confidence: 92%
See 2 more Smart Citations
“…The analyses were performed using CoulArray 5600A HPLC system (ESA Inc., Sunnyvale, CA, USA) and a model 526 UV detector (ESA Inc.) as previously described (Cui et al, 2009;Goldman et al, 2010). Chromatographic separation was achieved by using a Lichrospher 100 RP-18 column (5 mm, 250 mm  3 mm; Merck, KGaA, Darmstadt, Germany).…”
Section: High-performance Liquid Chromatography Analysis Of Purinesmentioning
confidence: 99%